A rice transcription factor, OsMADS57, positively regulates high salinity tolerance in transgenic Arabidopsis thaliana and Oryza sativa plants. Issue 3 (29th July 2021) - Wu, Junyu; Yu, Chunyan; Huang, Linli; Gan, Yinbo
Abstract: MADS‐box transcription factors (TFs) play indispensable roles in various aspects of plant growth, development as well as in response to environmental stresses. Several MADS‐box genes have been reported to be involved in the salt tolerance in different plant species. However, the role of the transcription factor OsMADS57 under salinity stress is still unknown. Here, the results of this study showed that OsMADS57 was mainly expressed in roots and leaves of rice plants ( Oryza sativa ). Gene expression pattern analysis revealed that OsMADS57 was induced by NaCl. Overexpression of OsMADS57 in both Arabidopsis thaliana (A. thaliana) and rice could improve their salt tolerance, which was demonstrated by higher germination rates, longer root length and better growth status of overexpression plants than wild type (WT) under salinity conditions. In contrast, RNA interference (RNAi) lines of rice showed more sensitivity towards salinity. Moreover, less reactive oxygen species (ROS) accumulated in OsMADS57 overexpressing lines when exposed to salt stress, as measured by 3, 3′‐diaminobenzidine (DAB) or nitroblue tetrazolium (NBT) staining. Further experiments exhibited that overexpression of OsMADS57 in rice significantly increased the tolerance ability of plants to oxidative damage under salt stress, mainly by increasing the activities of antioxidative enzymes such as superoxide dismutase (SOD) and peroxidase (POD), reducing malonaldehyde (MDA) content and improving the expression of stress‐related genes. Taken together, these results demonstrated that OsMADS57 plays a positive role in enhancing salt tolerance by activating the antioxidant system.